Spectroscopic investigation of PF-1000 discharges under different experimental conditions - Kubkowska, M.; Jakubowska, K.; Skladnik-Sadowska, E.; Malinowski, K.; Paduch, M.; Sadowski, M.J.; Scholz, M.; Marchenko, A.K. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
The emission from free-propagating plasma streams was studied in experiments with a 1-MJ plasma-focus PF-1000 facility operated at the IPPLM in Warsaw, Poland. The machine was filled up with a pure deuterium or a mixture of deuterium and argon. Optical spectra were recorded at a distance of 30 cm from the electrodes, at different experimental conditions, i.e. initial pressures, charging voltages and acquisition times, in the wavelength range of 350…1000 nm. The most intense lines originated from the applied working gases. In some cases distinct CuI and FeI lines resulted from the electrodes and the insulator were observed. From the Balmer lines, Dβ and Dγ, an electron density as a function of time was estimated. The application of this finding made it possible to perform some experiments concerning spectroscopic research on the interaction of free-propagating plasma streams with tungsten targets. In the recorded spectra some WI and WII lines were identified, but the resolution of the spectrometer was not good enough for their quantitative analysis. Исследовано излучение свободно распространяющихся плазменных потоков, генерируемых мегаджоульным плазменным фокусом ПФ-1000 (ИФПЛМ, Варшава, Польша). В качестве рабочего газа использовался чистый дейтерий и смесь дейтерия с аргоном. Оптические спектры в диапазоне 350...1000 нм регистрировались на расстоянии 30 см от электродов при вариации экспериментальных условий (начального давления, напряжения и времени обработки). Наиболее интенсивными спектральными линиями, зарегистрированными в экспериментальных спектрах, являются линии рабочего газа. В некоторых случаях наблюдались также линии примесных элементов: CuI – материала электродов и FeI – изолятора. Временная зависимость электронной плотности плазмы оценивалась из уширения бальмеровских линий Dβ и Dγ. Представлены также результаты спектрального анализа процесса взаимодействия плазменных потоков с вольфрамом. Идентифицированы спектральные линии WI и WII, однако разрешение спектрометра не позволило провести количественный анализ. Досліджено випромінювання плазмових потоків, що генеруються мегаджоульним плазмовим фокусом ПФ-1000 (ІФПЛМ, Варшава, Польща). В якості робочого газу використовувався чистий дейтерій і суміш дейтерію з аргоном. Оптичні спектри в діапазоні 350...1000 нм реєструвалися на відстані 30 см від електродів при варіації експериментальних умов (початкового тиску, напруги і часу обробки). Найбільш інтенсивними спектральними лініями, зареєстрованими в експериментальних спектрах, є лінії робочого газу. У деяких випадках спостерігались також лінії домішкових елементів: CuI – матеріалу електродів і FeI – ізолятора. Часова залежність електронної густини плазми оцінювалась з розширення бальмерівських ліній Dβ та Dγ. Представлено також результати спектрального аналізу процесу взаємодії плазмових потоків з вольфрамом. Ідентифіковано спектральні лінії WI і WII, проте роздільність спектрометра не дозволила провести кількісний аналіз.